Composite of hierarchical interpenetrating 3D hollow carbon skeleton from lotus pollen and hexagonal MnO2 nanosheets for high-performance supercapacitors1. Issue 18 (14th May 2015) - Li, Hongpeng; Wang, Bin; He, Xinyi; Xiao, Jun; Zhang, Hongseng; Liu, Qi; Liu, Jingyuan; Wang, Jun; Liu, Lianhe; Wang, Peng
<x xml:space="preserve">Abstract</x> Hierarchical and interpenetrating three-dimensional (3D) hollow MnO2/C composites have been successfully prepared via a facile and rapid dipping method.